Can a flexible surgical robot be used in the pediatric population: A feasibility study. (August 2022) - Goyal, Neerav; Goldenberg, David; Ruszkay, Nicole; Tucker, Jacqueline; May, Jason; Wilson, Meghan N.
Abstract: Objectives: Transoral robotic surgery in adults confers excellent results and decreased morbidity. Application of these techniques has not yet been rigorously investigated in children. The goal of this study is to evaluate the feasibility of a flexible robotic surgical system in a pediatric population. Methods: This was a non-randomized, non-blinded, prospective clinical trial. An Investigational Device Exemption was obtained from the FDA. Patients 8–12 years old scheduled for tonsillectomy and adenoidectomy between February and December 2019 at an academic tertiary care children's hospital were included. Exclusion criteria included pulmonary or vascular conditions posing risks for extended anesthesia, or a smaller mouth opening than the instrumentation (28 mm × 15 mm). Tonsillectomy was completed with standard monopolar cautery. After the surgery was complete, the robot was utilized for evaluation and assessment of exposure. A pediatric anesthesiologist screened patients for tolerance of additional anesthesia (up to 15 min). A flexible robotic surgical system, the MedRobotics Flex® Robotic System, was used to visualize and access the tonsillar fossa, posterior pharynx, base of tongue, epiglottis and false vocal folds. Visualization and access were graded on a five-point Likert scale. Results: A total of ten patients, eight males and two females, with obstructive sleep apnea (OSA) or sleep disordered breathing (SDB) were recruited in 2019. One patient did not complete the study due to equipment malfunction. The average patient demographics were: age 10.1 years (8.6–11.8 years), height 142.4 cm (127–164.9 cm), weight 47.5 kg (24.4–84.5 kg), and BMI 22.6 (13.9–31.0). Study time averaged 10.3 min (5–13 min). The tonsillar fossa, base of tongue, and posterior pharynx were visualized completely and easily accessed with the robotic instruments. The epiglottis and false vocal folds were visualized and accessed in 66% and 55% of patients, respectively. There were no adverse effects. Conclusions: This study demonstrated that a flexible robotic surgical system is feasible for use in children 8–12 years of age when performing otolaryngology - head and neck surgery procedures of the oropharynx and larynx. Highlights: Robotic surgery provides benefits such as increased precision and visualization. The oropharynx, hypopharynx, and larynx were successfully visualized and accessed. A flexible surgical robot is feasible for otolaryngology procedures in children.